2015
DOI: 10.3390/ph8040675
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction and Disturbed Coherence: Gate to Cancer

Abstract: Continuous energy supply, a necessary condition for life, excites a state far from thermodynamic equilibrium, in particular coherent electric polar vibrations depending on water ordering in the cell. Disturbances in oxidative metabolism and coherence are a central issue in cancer development. Oxidative metabolism may be impaired by decreased pyruvate transfer to the mitochondrial matrix, either by parasitic consumption and/or mitochondrial dysfunction. This can in turn lead to disturbance in water molecules’ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 81 publications
0
20
0
3
Order By: Relevance
“…Certainly, it has been long known that electrics fields affect cell function and shape: calcium has a strong effect on the electrical energy transfer and transistor-like properties of microtubules [70]. It has also been suggested that differences in mitochondrial function in cancer alter electric fields, in particular, affecting water order and coherence–which could be involved in the disease process [71]. Cancer is clearly associated with changes in mitochondrial dynamics and ultrastructure [72].…”
Section: The Quantum Mitochondrionmentioning
confidence: 99%
“…Certainly, it has been long known that electrics fields affect cell function and shape: calcium has a strong effect on the electrical energy transfer and transistor-like properties of microtubules [70]. It has also been suggested that differences in mitochondrial function in cancer alter electric fields, in particular, affecting water order and coherence–which could be involved in the disease process [71]. Cancer is clearly associated with changes in mitochondrial dynamics and ultrastructure [72].…”
Section: The Quantum Mitochondrionmentioning
confidence: 99%
“…In the vicinity of a single mitochondrion, the intensity of the electric field reduces almost linearly as a function of distance. Values of 540 kV/m for the electric field were measured at a distance of 2 µm from mitochondrion [5,6]. About 40% of the input chemical energy of the mitochondrion are converted into ATP and GTP, with the remaining 60% liberated from mitochondria as photons and heat [4].…”
Section: Endogenous Electromagnetic Field In the Cell: Published Hypomentioning
confidence: 99%
“…The oscillations generate EMF. The strong electrostatic field surrounding the mitochondria can move microtubule oscillations into highly nonlinear region [5]. Mitochondrial dysfunction in cancer cells (Warburg effect) or in fibroblasts associated with cancer cells (reverse Warburg effect) results in decreased or increased power of the EMF generated, respectively [5,7].…”
Section: Endogenous Electromagnetic Field In the Cell: Published Hypomentioning
confidence: 99%
“…protein) would be between 2-3 nm, which equates to about 7 to 10 layers of water molecules (Cameron and Fullerton 2014). Pokorný et al, based on work of others including (Stebbings and Hunt 1982), describe "empty layers" measuring 5-20 nm around microtubules with the ability to exclude solutes (Pokorný et al 2015). Collectively these studies imply that so-called "non-bulk" water may "jacket" all biologically-active molecules and membranes, including intracellular organelles, mitochondria, DNA and RNA.…”
Section: Introductionmentioning
confidence: 99%